STRATEGY OF UKRAINE’S PARTICIPATION IN INTERNATIONAL QUOTA MARKET OF GREENHOUSE GASES EMISSION - Berezyuk, Roman; Kitura, Andriy (Journal of European Economy, 2017)
Theoretical aspects of national strategy are studied for Ukraine’s participation in the functioning of international quota market of greenhouse gases emission. The effect of time factor produced on the efficiency of transactions with quotas is clarified. The market mechanisms which are preferential from national positions are substantiated.